2002
DOI: 10.1034/j.1600-051x.2002.291203.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of apoptotic and proliferative gingival keratinocytes in oral and sulcular epithelium in patients with gingivitis and periodontitis

Abstract: These showed that 5-12% of the keratinocytes in the basal layers of the epithelium proliferated in the two groups. Fewer apoptotic cells were seen in the oral epithelium than in the sulcus in all subjects in both groups. Only in the most apical part of the sulcus, close to the junctional epithelium, did the number of apoptotic keratinocytes exceed the proliferative ones in patients with periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 26 publications
(34 reference statements)
2
48
0
Order By: Relevance
“…Among other effectors of the apoptotic response, the products of p53 and Bcl-2 proteins have been shown to play fundamental roles (Handfield et al 2005;Mao et al 2007;Tonetti Cortellini and Lang 1998a;Vaux Cory and Adams 1988). Emerging evidence supports the concept that bacterium-modulated apoptosis is a relevant phenomenon in the pathogenesis of periodontal diseases (Arakawa et al 2000;Bantel et al 2005a;Chen and Zychlinsky 1994;Graves Jiang and Genco 2000;Jarnbring et al 2002;Kato et al 1995;Tonetti Cortellini and Lang 1998a;Tonetti Cortellini and Lang 1998b;Vitkov Krautgartner and Hannig 2005;Wang et al 1999).…”
Section: Apoptosismentioning
confidence: 83%
“…Among other effectors of the apoptotic response, the products of p53 and Bcl-2 proteins have been shown to play fundamental roles (Handfield et al 2005;Mao et al 2007;Tonetti Cortellini and Lang 1998a;Vaux Cory and Adams 1988). Emerging evidence supports the concept that bacterium-modulated apoptosis is a relevant phenomenon in the pathogenesis of periodontal diseases (Arakawa et al 2000;Bantel et al 2005a;Chen and Zychlinsky 1994;Graves Jiang and Genco 2000;Jarnbring et al 2002;Kato et al 1995;Tonetti Cortellini and Lang 1998a;Tonetti Cortellini and Lang 1998b;Vitkov Krautgartner and Hannig 2005;Wang et al 1999).…”
Section: Apoptosismentioning
confidence: 83%
“…Apoptosis is a highly regulated form of programmed cell death, defined by distinct morphological and biochemical features (Vaux and Strasser, 1996;Peter et al, 1997b). Abnormal apoptosis has been implicated in various pathologies, e.g., cancer, AIDS, Alzheimer's disease, rheumatoid arthritis (Thompson, 1995;Peter et al, 1997a;, periodontal diseases (Tonetti et al, 1998;Jarnbring et al, 2002;Bantel et al, 2005), and diabetes (Alikhani et al, 2005a;Graves et al, 2006). Apoptosis can be modulated by mediators of inflammation (Dalgleish and O'Byrne, 2006;Graves et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Another contributing factor for periodontal tissue destruction is reported to be the induction of host cell apoptosis by specific subgingival plaque pathogens (5). In gingival biopsies from patients with chronic periodontitis, apoptotic cells have been reported to constitute about 10% of the total cell population and included epithelial and fibroblast cells (31,36). Tonetti et al (86) have reported that exposure of clinically healthy gingival tissues to plaque bacteria induces apoptosis-associated DNA damage and the expression of proapoptotic p53 protein.…”
mentioning
confidence: 99%
“…Tonetti et al (86) have reported that exposure of clinically healthy gingival tissues to plaque bacteria induces apoptosis-associated DNA damage and the expression of proapoptotic p53 protein. Furthermore, in gingival biopsies from patients with periodontitis, epithelial cell apoptosis was reported to be more prevalent in the most apical part of the sulcus closest to the subgingival plaque (31,86). These observations suggest that interactions with certain bacterial products may play an important role in inducing apoptosis in gingival tissue cells.…”
mentioning
confidence: 99%